Strategi Smart Test Dalam Pembelajaran Latsar CPNS di Era Society 5.0 - Agus Suharsono; Ana Uluwiyah (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2020)
An important point in community 5.0 is cross-section based on knowledge and information, thus encouraging people to be able to continue to grow and develop into active community people. The concept in society 5.0, has begun to develop in the culture of Indonesian society. There are several important indicators, including public awareness to use IT as an